Development of Learning Media Based on Google Sites on the Material I Am a Pancasila Student for Third Grade Elementary School Students - Kurniawati, Selpina; Hadikusuma Ramadan, Zaka (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study focuses on obtaining valid Google Sites media, so it is said to be suitable for use in the learning process. This research aims to create interactive media based on Google Sites for the “ I am a pancasila student” material in grade 3 of elementary school during learning activities. This study is a research and development type, utilizing the simplified ADDIE model, which includes the stages of analysis, design, and development. The data collected in this development are both qualitative and quantitative. The trial was conducted on a small scale, with a sample of 10 student’s representing various learning achievement categories. Data collection techniques involved two instruments: first, questionnaires for teacher and students, and second, validation sheets for material experts, media experts, and language experts. Based on study’s results, media experts scored 90.83% material experts 99.16% and language experts 100% with an overall validity score of 90.32%,indicating that the media is highly valid for use as a learning tool. Teacher responses and student responses experts both scored 100% resulting in an overall score of 100% categorized as “very valid”. Google Sites-based learning media developed is valid suitable for use in learning activities.